Reconstruction of scalp with local axial flaps - Srivastava, Saket; Gupta, Pradeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The scalp is a unique part of the human body and various etiological factors, such as tumour extirpation, infection, burns, or trauma, can lead to scalp defects. Primary closure, skin grafting, local flaps, tissue expansion or free tissue transfer are modalities available for scalp reconstruction. In this article, the authors share their institutional experience using various local flaps concerning the size, location, depth of defect and the quality of surrounding tissue. Methods: From September 2017 to January 2020, 54 patients underwent scalp reconstruction with local flaps for a defect size of 5 to 150 cm2 in the department of plastic surgery, SMS medical college, Jaipur. Patients were identified by age, sex, cause of the scalp defect; the location, size, and depth of the defect; condition of surrounding tissue and the type of reconstruction done. Results: The most common cause of scalp defect was excision of malignant tumour (50%). Thirty patients had a large sized defect (40-90 cm2) and 28 patients had 90-150 cm2 defects. Surgical reconstruction was done using local flaps, transposition flap was the most used in 36 patients (66.7%) followed by rotation advancement flap in 11 patients (20.4%). The recovery was relatively quick. Minor complications happened in 5 patients (9.3%) that were managed conservatively. Conclusions: In the present era of microsurgical reconstruction, local options as axial flaps provide a simpler and safer method of scalp reconstruction. A carefully planned scalp flap gives healthy, robust, hair-bearing tissue coverage and requires a shorter healing time for the patients.